Monitoring productivity of Kazakh Bactrian and Arvana camels of Kazakhstan population. Issue 1 (November 2020) - Baimukanov, A; Alibayev, N; Semenov, V; Ermakhanov, M; Abuov, G
Abstract: The purpose of the study is to perform monitoring of camels of Kazakh Bactrian and Arvana dromedary breeds in the South West region of Kazakhstan; to determine perspective genotypes of purebred camels according to their dairy productivity. The study of class composition of the selected Arvana female camels of the 1 st lactation with a milk yield of not less than 1950 kg allowed identifying 21.8% of Elite Class and 78.2% of Class I among 125 animal units. Kazakh Bactrian female camels of the first lactation are also selected with the yield of 1000 kg minimum in the number of 309 animals in the basic collective farms of camel breeding zones. It was found out that of 309 animals, 23.0% compose the Elite Class and 77.0% make the Class I. The estimation of Kazakh Bactrian female camels according to the milking capacity coefficient allowed determining that the optimal parameter for selection is Rank 1.5-1.9. It was found that in female camels according to the fertility index of Rank 1 (up to 42%), colt safety is reliably higher that compared with female camels of the same age with Rank 2 (42-47%) and Rank 3 (47% and higher).